2021
DOI: 10.1016/j.psj.2021.101169
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and molecular characterization of avian infectious bronchitis virus in southern China

Abstract: Avian infectious bronchitis virus ( IBV ) is causing considerable economic losses in the world poultry industry. The main difficulty of prevention and control of IB disease is the numerous genotypes and serotypes. The genetic analysis of IBV was mainly based on the S1 gene which played an important role in infectivity. In the study, One hundred and thirty-nine strains of avian infectious bronchitis virus were isolated from chickens showing signs of disease in southern China during the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 46 publications
0
6
1
1
Order By: Relevance
“…In addition, most phylogenetic analyses of IBV are also based on the S1 gene, which has 3 HVRs that provide a platform for genetic evolution ( Valastro et al, 2016 ). In this study, genetic evolution and homology analysis based on the S1 gene showed that the newly identified strains ZH01 and HH09 belong to the GI-19 lineage in QX genotype, which still remains as the most dominant genotype of IBV circulating in southern China ( Lian et al, 2021 ). Novel mutations such as T273I, T292A, and S331K were found in the emerging IBV strains and further studies based on reverse genetic techniques are needed to study their role in the biology of IBV.…”
Section: Discussionmentioning
confidence: 83%
“…In addition, most phylogenetic analyses of IBV are also based on the S1 gene, which has 3 HVRs that provide a platform for genetic evolution ( Valastro et al, 2016 ). In this study, genetic evolution and homology analysis based on the S1 gene showed that the newly identified strains ZH01 and HH09 belong to the GI-19 lineage in QX genotype, which still remains as the most dominant genotype of IBV circulating in southern China ( Lian et al, 2021 ). Novel mutations such as T273I, T292A, and S331K were found in the emerging IBV strains and further studies based on reverse genetic techniques are needed to study their role in the biology of IBV.…”
Section: Discussionmentioning
confidence: 83%
“…Another aspect to note is the relatively high identity of the Tanzanian virus to the Asian GI-7 IBVs, and their monophyletic clustering with GI-19 IBVs. Like the GI-19, GI-7 IBVs were also first identified in China in the 1990s and subsequently became the third-most prevalent genotype in the country, but there is no documented evidence of their detection outside of China and Taiwan [17,66,67]. Further, there are reports of recombination between GI-7 and GI-19 genotypes, as well as between the two genotypes and field/vaccine strains belonging to different genotypes [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…The S1 gene sequences of 60 South Korean IBV isolates were analyzed, and it was discovered that in addition to the GI-15 and GI-19 IBV lineages, five other subgroups of GI-19 cocirculated and expanded in South Korea ( Lee et al., 2021 ). Since its discovery in 1996, Lineage GI-19 (QX-type) has been the most prevalent IBV strain in China 1996 ( Feng et al., 2017 ; Xu et al., 2018 ) Furthermore, GI-7 (TW-type) and GI-13 (4/91-type) lineages have been recognized to be significant IBV strains in China, with rare infections of GI-1 (Mass-type), GI-9 (Ark-type), and GI-28 (LDT3-type) also reported ( Zhao et al., 2016 ; Lian et al., 2021 ). The latest studies found 19 IBV variants in clinical specimens collected in China amid January 2021 and June 2022; these included 12 variants of GI-19, three variants of GI-7, and one each of GI-1, GI-9, GI-13, and GI-28.…”
Section: Genotypic Prevalence On Continentsmentioning
confidence: 99%